Internationalization, design and global development 4th International Conference, IDGD 2011, Held as part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings (Lecture notes in computer science, 2011)
This volume constitutes the refereed proceedings of the 4th International Conference on Internationalization, Design and Global Development, IDGD 2011, held in Orlando, FL, USA, in July 2011 in the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011. The 71 revised papers presented were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the entire field of internationalization, design and global development and address the following major topics:  Cultural and cross-cultural design, culture and usability, design, emotion, trust and aesthetics, cultural issues in business and industry, culture, communication and society.